ANTIBACTERIAL AND ANTIFUNGAL ACTIVITY OF LEAVES OF THESPESIA POPULNEA - Krishnamoorthy, Shanmugam; Adaikala Raj, Gnanaprakasam; Chandrasekaran, Manivachagam; CHANDRASEKARAN, MANIVACHAGAM (International Journal of Pharmacy and Pharmaceutical Sciences, 2014)
Objective: To find out the antibacterial and antifungal activity of T. populnea leaves against bacterial and fungal strains. Methods: T. populnea leaves were extracted successively with different solvents viz., hexane, chloroform, ethyl acetate and methanol. Solvent extracts were screened for antimicrobial activity against bacterial strains such as, gram positive and gram negative bacterial and fungal strains such as., Aspergillus spp. and dermatophytic strains by disc diffusion method, determination of Minimum Inhibitory Concentration (MIC), Minimum Bactericidal Concentration (MBC) and Minimum Fungicidal Concentration (MFC). Results: In bacterial screening, chloroform extract of leaves of T. populnea showed the highest antibacterial activity against Staphylococcus aureus and the mean zone of inhibition was 14.8 mm. The lowest MIC and MBC values were 62.5 and 125 µg/ml respectively. In fungal screening, methanol extract showed the highest antifungal activity against Aspergillus fumigatus and the mean zone of inhibition was 22.8 mm. The lowest MIC (62.5 µg/ml) and MFC (125 µg/ml) values were observed against A. fumigatus and Microsporum gypseum. Phytochemical analyses of different extracts of leaves of T. populnea were analysed. The methanol extract of T. populnea leaves showed the presence of strong phytochemicals viz., flavonoids, tannins, steroids, glycosides, saponins, phenols, terpenoids and alkaloids than other extracts. Conclusion: T. populnea has antimicrobial activity and the chloroform and methanol leaf extracts are useful sources of antimicrobial agents and for further pharmacological studies towards bacterial and fungal infections.